Evaluation and Management in the Upper Great Marsh: Emergent Phragmites Australis. - Ringelheim, Jenna.; Filosa, Gina.; Baumann, Lauren; Astle, Jay. (Tufts University. Tisch Library., 2018)
2005 M.A. in Urban and Environmental Policy and Planning Field Project. Client: Eight Towns and the Bay/Merrimack Valley Planning Commission.